2011
DOI: 10.3233/jad-2011-111010
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Conversion of Omega-6 into Omega-3 Fatty Acids Improves Neuropathology in an Animal Model of Alzheimer's Disease

Abstract: Dietary supplementation with n-3 polyunsaturated fatty acids (n-3 PUFA) reduces amyloid-β (Aβ) and tau pathology and improves cognitive performance in animal models of Alzheimer's disease (AD). To exclude confounding variables associated with the diet, we crossed 3 × Tg-AD mice (modeling AD neuropathology) with transgenic Fat-1 mice that express the fat-1 gene encoding a PUFA desaturase, which endogenously produces n-3 PUFA from n-6 PUFA. The expression of fat-1 shifted the n-3:n-6 PUFA ratio upward in the bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 0 publications
2
43
0
1
Order By: Relevance
“…The ratio of positive PHF-stained cells was 0/100 for control, 18/100 for repeat-blast, and 3/100 for repeatblast+DHA animals (chi-square test 26.571 with 2 degrees of freedom, p < 0.0001). The ratio of positive CP-13-stained cells for controls was 0/100, for repeat blast it was 17/100, and for repeat-blast+DHA it was 4/100 (chi-square test 22.571 with 2 degrees of freedom, p < 0.0001). In addition, H & E staining revealed a heterogeneous appearance, chromatolysis, vacuolization, and degenerating neurons 3 weeks after repetitive blasts but not in control or repeatblast+DHA animals ( Fig.…”
Section: Results Tau Pathology Is Evident In Blast-injured Animals Anmentioning
confidence: 99%
See 1 more Smart Citation
“…The ratio of positive PHF-stained cells was 0/100 for control, 18/100 for repeat-blast, and 3/100 for repeatblast+DHA animals (chi-square test 26.571 with 2 degrees of freedom, p < 0.0001). The ratio of positive CP-13-stained cells for controls was 0/100, for repeat blast it was 17/100, and for repeat-blast+DHA it was 4/100 (chi-square test 22.571 with 2 degrees of freedom, p < 0.0001). In addition, H & E staining revealed a heterogeneous appearance, chromatolysis, vacuolization, and degenerating neurons 3 weeks after repetitive blasts but not in control or repeatblast+DHA animals ( Fig.…”
Section: Results Tau Pathology Is Evident In Blast-injured Animals Anmentioning
confidence: 99%
“…In addition, DHA has recently been shown to readily enter the brain and inhibit neurofibrillary tangle formation in a murine model of Alzheimer's disease. 13,22 Linking these two important properties of DHA is a topic of ongoing investigation.…”
Section: Discussionmentioning
confidence: 99%
“…52 Outros estudos em humanos e animais suportam a noção de que a razão n-6 / n-3 está associada com risco de demência e declínio cognitivo, e o menor consumo de n-3 poderá acelerar entre 10% e 80% o declínio cognitivo. [19][20][21][22][23][24] Nunes B, et al Ómega-3, razão ómega-6 / ómega-3 e função cognitiva, Acta Med Port 2017 Mar;30(3):213-223 Tabela 5 -Associação entre o índice ómega-3 e a razão ómega-6 / ómega 3 e compromisso em domínios específicos…”
Section: Discussionunclassified
“…In addition, overexpression of Fat-1, enhancing endogenous production of n-3 PUFAs, in 3×Tg-AD mice significantly reduces phosphorylated tau and improves brain function [106] . Although the reasons for these disparities are unclear, it is probable that different stages of AD have different effects on fatty-acid metabolism, or gene expression for fatty-acid synthesis differs during different stages.…”
Section: Role Of Fatty-acid Metabolism In Ad Pathogenesismentioning
confidence: 99%
“…However, recent in vivo studies using an APP mutant AD mouse model showed that both extraneously supplied and endogenous PUFAs suppress Aβ production and the formation of amyloid plaques [106] . Similarly, MUFAs, mainly oleic acid, inhibit the production of Aβ and amyloid plaque formation both in vitro and in vivo [90] .…”
Section: Role Of Fatty-acid Metabolism In Ad Pathogenesismentioning
confidence: 99%